Hukum dan Sanksi Terhadap Pelaku Pembabatan Hutan: Analisis Kasus dan Implikasi - M. Rami Ramadhan; Syamsuddin Syamsuddin (Juris Prima: Jurnal Inovasi Hukum dan Kebijakan, 2026)
Indonesia's tropical forests continue to shrink due to rampant illegal logging, despite the enactment of legal instruments such as the Forestry Law and the Law on the Prevention and Eradication of Forest Destruction (P3H). This study aims to analyze the regulatory framework of sanctions for forest clearing in Indonesia, evaluate the effectiveness of its law enforcement through the analysis of court decisions, and identify the implications of such enforcement weaknesses. This study employs a normative juridical method utilizing statutory and case approaches. The analysis reveals a disparity in law enforcement within the courtroom; criminal sanctions tend to be harshly applied to field laborers but fail to ensnare intellectual actors and corporate entities due to the complexity of proving malicious intent (mens rea). Furthermore, the paradigm shift prioritizing administrative sanctions following the enactment of the Job Creation Law potentially reduces the deterrent effect of the law. This weak enforcement has severe impacts on ecological degradation, the escalation of agrarian social conflicts, and state financial leakage. As a solution, this study recommends the stricter application of the strict liability principle for corporations and the cumulative integration of environmental restoration obligations within judicial verdicts.